The association of dementia risk symptoms and functional activity in adults with Down syndrome - Selena E. Washington; Amy E. Bodde; Brian C. Helsel; Rebecca M. Bollinger; Nora Smith; Lauren T. Ptomey; Beau Ances; Susan L. Stark (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Adults with Down syndrome (DS) have an increased risk of Alzheimer's disease (AD) dementia, often showing neuropathological indicators by age 40. Physical function and activities of daily living (ADLs) are understudied areas of function that may inform dementia risk. We investigated associations among age, physical function (gait/balance, grip strength, and lower extremity strength), ADLs, and dementia risk symptoms in adults with DS. We hypothesized that compromised physical function and lower independence with ADLs would be associated with an informant/caregiver‐reported measure of dementia risk symptoms. METHODS A secondary analysis for this cross‐sectional study was completed using data from two academic research centers with 43 adults with DS (age 30 ± 12 years). We examined the association of dementia risk symptoms, captured through the Dementia Screening Questionnaire for Individuals with Intellectual Disabilities (DSQIID), with physical function (timed up and go [TUG], sit‐to‐stand [STS], grip strength) and ADLs (Waisman Activities of Daily Living Scale). A linear regression model for the continuous dementia risk measure in the DSQIID used a log transformation of (1 + log(Y + 1)) to account for a high zero count. Wilcoxon rank‐sum tests were used to assess differences in the physical function measures, DSQIID questionnaire, and Waisman ADL by dividing mean age categories. RESULTS Higher DSQIID scores were associated with lower independence with ADLs (β = −0.103, p = 0.008), slower gait times (TUG; β = 0.112, p = 0.034), and impaired lower extremity strength (STS; β = 0.112, p = 0.017) and grip strength (β = −0.039, p = 0.034). DSQIID scores differed significantly between the ≥30 and <30 age groups. Participants ≥30 years of age scored 5 points higher on the DSQIID than participants <30, suggesting that age was associated with greater dementia risk. DISCUSSION Greater dementia risk symptoms were associated with age, lower physical function scores, and independence with ADLs, suggesting that declines in physical function and ADLs may be early indicators of subsequent dementia risk in adults with DS. Highlights We explored the association of physical function and activities of daily living (ADLs) in aging adults with DS and their relationship with informant/caregiver report of dementia risk symptoms. Our findings demonstrated a significant relationship between a higher number of dementia risk symptoms observed and lower independence with ADLs, and impaired gait/balance, grip strength, and lower extremity strength. Further research with larger longitudinal studies is necessary to investigate any causative relationships among physical function, ADL function, and dementia risk symptoms.